Communication and supply chain processes: a systematic content analysis of the international debate. Issue 2 (5th May 2015) - Gambetti, Rossella C.; Biraghi, Silvia; Giovanardi, Mattia; Gregory, Anne; Gregory, Anne
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose Our study is aimed at identifying how communication has been approached in the Supply Chain (SC) literature debate focused on relationship-based processes over the last decade, in order to find out whether different communication approaches exist and, if they do, to distinguish their specific features. Design/methodology/approach We carried out a systematic software-assisted content analysis of the SC relationship-based literature debate that allowed illustrating and classifying communication approaches and viewpoints developed in SC studies. This content analysis combined rigorous linguistic and statistical analyses performing a less biased review of the debate than the traditional literature desk-analysis. Findings Communication emerged as a key managerial practice associated to SC performance topics related to efficiency and effectiveness of exchanges among internal business units and external business partners. Communication also appeared as a key embedded component of SC relationships, which can act as a negotiation and an alignment element in trade-off dynamics between the company and its strategic partners. Finally, communication emerged as a cultural asset of the company, that serves to establish, widespread and nurture shared ethical values and principles regarding SC quality and service standards. Practical implications Our analysis pointed out associative dimensions, thematic specificities and managerial approaches related to communication along the SC that helped reflecting on how communication practices can be concretely oriented by SC executives to achieve better SC performances, enhancing SC contribution to firm's competitive advantage. Originality/value Our study provides an original contribution to knowledge development in the field of corporate communication management, since beyond analysing communication in the "corporate locus" of the typical communication department, we believe it is valuable to develop a cross-functional approach, exploring the value of communication which is "embedded" in manufacturing processes and routines characterizing the SC of a company.